International trade and tourism for Mediterranean countries: A panel causality analysis - Ceyhun Can OZCAN (Theoretical and Applied Economics, 2016)

(untitled)
This paper examines the causal relationship between international trade and tourism for 16 Mediterranean countries period from 1995 to 2013. We employ the recently introduced panel Granger causality approach that is flexible enough to take account of both cross-country correlation and heterogeneity across the countries. The empirical results indicate the causality from export to tourism in four out of sixteen Mediterranean Economies.